ANALYSIS DU PONT SYSTEM IN MEASURING FINANCIAL PERFORMANCE IN COSMETIC COMPANIES AND HOUSEHOLD REQUIREMENTS LISTED ON THE IDX IN 2017-2021 - RAHMA FADILA; NELVA SISKAWATI (Indragiri Research Center (ingreat), 2023)
This research was conducted at Companies in the Cosmetics and Household Needs Sector that were listed on the Indonesia Stock Exchange (IDX) for 2017-2021. This study aims to determine the Financial Performance of Cosmetic Companies and Household Uses using DuPont System analysis. Analysis of the Du Pont System can explain a company's financial performance and shows the location of the strengths and weaknesses of a company in which there are several financial ratios used in this study including Net Profit Margin, Total Assets TurnOver, and Return On Assets (Du Pont). The data analysis technique used is quantitative descriptive analysis. The population and sample in this study are 6 cosmetics and household goods companies listed on the Indonesia Stock Exchange in the 2017-2021 period. The results showed that the financial performance of Cosmetics and Household Supplies companies for 5 years which was calculated using the Du Pont System analysis was not good enough, with ROA values ​​that decreased every year except for PT. Akasha Wira International Tbk (ADES) has an ROA value that increases every year. The decrease in the value of ROA was due to a decrease in the value of NPM and TATO. This situation is affected by a decrease in profits due to high total costs and slow turnover of assets to increase sales.